Pengaruh Auditor Switching, Reputasi Kantor Akuntan Publik, Dan Audit Tenure Terhadap Kualitas Audit Dengan Efektivitas Komite Audit Sebagai Variabel Moderasi (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di BEI Periode 2018-2023) - Lia Arizki; Yani Suryani; Desi Ika (Cattleya Darmaya Fortuna, 2025)
This research aims to determine auditor switching, Public Accounting Firm reputation, and audit tenure on audit quality with the effectiveness of the audit committee as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange in 2018 - 2023. The sample selection method used is purposive sampling. The total observations in this research were 264 samples with 6 years of observation consisting of 44 companies. The data analysis technique used in this research is logistic regression analysis and Moderated Regression Analysis. The test results of this research indicate that auditor switching, Public Accounting Firm reputation, and audit tenure simultaneously or together have an effect on audit quality. Partially, auditor switching has a significant positive effect on audit quality, audit tenure has a significant negative effect on audit quality, and KAP reputation has no effect on audit quality. The effectiveness of the audit committee is able to moderate the effect of KAP reputation and audit tenure on audit quality. The effectiveness of the audit committee is unable to moderate the effect of auditor switching on audit quality.